A RARE CASE OF CERVICAL LEIOMYOSARCOMA: CASE REPORT AND COMPREHENSIVE MANAGEMENT AT PHC SURABAYA HOSPITAL - Noorlaksmiatmo, Harno Prihadi (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2024)
Introduction: Cervical cancer is a malignant neoplasm that grows from cells originating from the cervix in the uterus. Leiomyosarcoma is a type of neck cancer that is relatively rare, data from the USA shows an incidence rate of only 0.35-0.64 per 100,000 women.Objective: This paper reports on the management of leiomyosarcoma cases at PHC Surabaya Hospital.Case Report: A 45-year-old female patient complained of continuous menstruation. An ultrasound was performed, and a biopsy was planned due to the mass found during the ultrasound. The biopsy showed cervical malignancy. A total hysterectomy, and bilateral oophorectomy, were performed and a PA examination was carried out on the uterine samples resulting from the operation the results, were leiomyosarcoma, high-grade, cervix, invasion in the stroma of the parametrium, vaginal cuff and both sides of the lymph nodes were free of tumor (pt1b3 n0mx)Conclusion: The patient was treated for 3 days at PHC Hospital after surgery and went home without complications from the surgical wound. The patient returned to control after 6 months with signs of tumor recurrence and negative metastases.